Distribution of nontuberculous mycobacteria in treated patients with pulmonary disease in Greece – relation to microbiological data. (August 2015) - Manika, Katerina; Tsikrika, Stamatoula; Tsaroucha, Emilia; Karabela, Simona; Karachaliou, Iris; Bosmi, Ioulia; Kioumis, Ioannis; Papavasileiou, Apostolos
Aims. The aim was to assess the distribution of nontuberculous mycobacteria (NTM) in treated patients with pulmonary disease (PD) in Greece.Patients & methods. Patients treated for NTM PD at the two largest chest diseases hospitals in Greece, in the period 1990–2013 were investigated. For the years 2005–2013 data on NTM isolation frequency were recorded.Results. M. avium complex (MAC) was the predominant cause of NTM PD disease followed by M. kansasii and rapid growing mycobacteria (RGM). The pathogenicity of RGM was significantly lower than this of MAC and M. kansasii . An increase was observed in the percentage of isolated NTM species that were considered clinically significant over the study period.Conclusions. The increasing number of NTM PD in Greece is a consequence of their isolation being more frequently considered as clinically relevant.